Evaluation of free radical scavenging activity of leaf of Hypericum mysorense Heyne - Sornalakshmi V; Tresina PS; Paulpriya K; Veerabahu Ramasamy Mohan (International Journal of Phytomedicine, 2017)
Hypericum is a well-known plant genus in herbal medicine. Hypericum mysorense is well known in folklore medicine for its varied therapeutic potential. The in vitro antioxidant activity of petroleum ether, benzene, ethyl acetate, methanol and ethanol extract of leaf of Hypericum mysorense have been tested using various antioxidant model systems viz; DPPH, hydroxyl, superoxide, ABTS and reducing power. The scavenging effect increases with the concentration of standard and samples. Among the solvent tested, ethanol extract exhibited highest DPPH (116.33% inhibition), hydroxyl (101.84%), superoxide (116.09%) and ABTS (119.22%) radical scavenger activity. Methanol extract of H.mysorense shows the highest reducing ability. The aim and purpose of this study is to show the significant free radical scavenging potential of H.mysorense leaf which can be experimented for the treatment of various free radical mediated ailments